New Approaches to Target T-ALL - Roti, Giovanni; Stegmaier, Kimberly (Frontiers in Oncology, 2014)
Acute lymphoblastic leukemia (ALL) is the most common malignancy in children. Although it is now curable in 80-90% of cases, patients with T-ALL experience a higher frequency of induction failure and early relapse. Despite aggressive treatment approaches, including transplantation and new salvage regimens, most children with relapsed T-ALL will not be cured. As such, we are in need of new targeted therapies for the disease. Recent advances in the molecular characterization of T-ALL have uncovered a number of new therapeutic targets. This review will summarize recent advancements in the study of inhibiting the NOTCH1, PI3K-AKT and Cyclin D3:CDK4/6 pathways as therapeutic strategies for T-ALL. We will focus on preclinical studies supporting the testing of small-molecule inhibitors targeting these proteins and the rationale of combination therapies. Moreover, epigenetic approaches to modulate T-ALL are rapidly emerging. Here we will discuss the data supporting the role of BET bromodomain inhibitors in human T-ALL.